PENERAPANÂ METODEÂ BERMAINÂ PERANÂ UNTUKÂ MENINGKATKANÂ AKTIVITASÂ DANÂ HASILÂ BELAJARÂ SISWAÂ KELASÂ VÂ PADAÂ MATAÂ PELAJARANÂ IPSÂ POKOKÂ BAHASANÂ JENISâ€JENISÂ USAHAÂ EKONOMIÂ DIÂ SDNÂ NGADILUWIHÂ 02Â KEDIRIÂ - zulfa nairurohmah; Chumi Zahroul (Universitas Muhammadiyah Surabaya, 2016)
TheÂ SocialÂ ScientsÂ SubjectÂ learningÂ activitiesÂ inÂ SDNÂ NgadiluwihÂ 02Â KediriÂ yetÂ usingÂ a varietyÂ ofÂ learningÂ methods.Â AccordingÂ toÂ theÂ observationÂ ofÂ prasiklusÂ knownÂ thatÂ the activityÂ andÂ studentÂ learningÂ outcomesÂ haveÂ notÂ beenÂ includedÂ inÂ bothÂ criteria. PrecentationÂ ofÂ studentÂ activity inÂ theÂ prasiklusÂ inÂ highlyÂ activeÂ criteriaÂ is12%Â (3Â students), inÂ theÂ activeÂ criteriaÂ isÂ 16%Â (4Â students),Â inÂ theÂ quiteÂ activeÂ criteriaÂ isÂ 56%Â (14Â students),Â in theÂ lowÂ activeÂ criteriaÂ isÂ 16%Â (4Â students).Â TheÂ meansÂ ofÂ studentÂ learningÂ activityÂ in prasiklusÂ isÂ 56%Â (quiteÂ activeÂ criteria).Â PrecentationÂ ofÂ studentÂ learningÂ outcomesÂ inÂ the veryÂ goodÂ criteriaÂ isÂ 24%Â (6Â students),Â inÂ theÂ goodÂ criteriaÂ isÂ 24%Â (Â 6Â students),Â inÂ theÂ good enoughÂ isÂ 36%Â (9Â students),Â inÂ theÂ notÂ goodÂ isÂ 16%Â (4Â students).Â TheÂ meansÂ ofÂ student learningÂ outcomesÂ inÂ prasiklusÂ isÂ 68Â (goodÂ enoughÂ criteria).BasedÂ onÂ theseÂ findingsÂ the needÂ forÂ aÂ moreÂ variedÂ teachingÂ methodsÂ withÂ emphasisÂ onÂ studentÂ activityÂ andÂ provide opportunitiesÂ forÂ studentsÂ toÂ developÂ theirÂ learningÂ abilitiesÂ toÂ theÂ fullest.Â InÂ accordance withÂ theseÂ problems,Â theÂ goalÂ ofÂ thisÂ researchÂ isÂ toÂ improveÂ theÂ activityÂ andÂ student learningÂ outcomesÂ inÂ classÂ VÂ throughÂ theÂ applicationÂ ofÂ learningÂ methodsÂ RoleÂ PlayingÂ IPS HighlightsÂ TypesÂ ofÂ economicÂ activitiesÂ in SDNÂ NgadiluwihÂ 02Â Kediri.Â ThisÂ typeÂ ofÂ research isÂ classroomÂ actionÂ researchÂ (PTK)Â areÂ conductedÂ inÂ twoÂ cycles.Â TheÂ resultsÂ obtainedÂ inÂ this studyÂ indicateÂ thatÂ throughÂ theÂ implementationÂ ofÂ RoleÂ PlayingÂ methodÂ canÂ increaseÂ the activityÂ andÂ studentÂ learningÂ outcomes.Â TheÂ averageÂ activityÂ ofÂ studentsÂ inÂ prasiklusÂ is 56,4%Â (quiteÂ activeÂ criteria).Â InÂ theÂ firstÂ cycleÂ increasedÂ toÂ 70,8%Â (activeÂ criteria).Â InÂ the secondÂ cycleÂ increasedÂ againÂ toÂ 80,96%Â (highlyÂ activeÂ criteria).Â TheÂ meansÂ scoreÂ onÂ the studentÂ learningÂ outcomesÂ prasiklusÂ isÂ 68Â (criteriaÂ quiteÂ well).Â InÂ theÂ firstÂ cycleÂ increased toÂ 73.2Â (goodÂ criteria).Â InÂ theÂ secondÂ cycleÂ increased againÂ toÂ 83.18Â (veryÂ goodÂ criteria). Â Keywords:Â RoleÂ PlayingÂ Method,Â studentÂ lerningÂ activity,Â studentÂ learningÂ outcomes, classroomÂ actionÂ research. Â